2017
DOI: 10.1007/s13202-017-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

Selecting a potential smart water for EOR implementation in Asab oil field

Abstract: The IFT and contact angle are believed to have direct impact on wettability alteration of crude oil/water/rock systems. In this work, extensive laboratory work was conducted to investigate the effect of these two key parameters on wettability alteration at elevated temperature (90°C) and ambient conditions. Twenty-six brines representing various scenarios of dilution and sulphate spiking were prepared and tested to identify the smart water most effective in the alteration of wettability. Sea water (SW) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that the IFT between oleic and aqueous phases decrease due to chloride ion reduction from seawater. Hence, regarding the positive effect of chloride ion reduction in seawater on the oil recovery factor and the capability of NaOAc and KOAc salts in lowering IFT, the impact of seawater containing these salts in the absence of NaCl salt on oil production was investigated. The result of measured IFT between crude oil and different brines including synthetic SW, MSW.NaOAc, and MSW.KOAc is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that the IFT between oleic and aqueous phases decrease due to chloride ion reduction from seawater. Hence, regarding the positive effect of chloride ion reduction in seawater on the oil recovery factor and the capability of NaOAc and KOAc salts in lowering IFT, the impact of seawater containing these salts in the absence of NaCl salt on oil production was investigated. The result of measured IFT between crude oil and different brines including synthetic SW, MSW.NaOAc, and MSW.KOAc is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have been carried out to explain the mechanisms acting on oil in smart waterflooding. These mechanisms include the reduction of the IFT between aqueous and oleic phases, rock surface wettability alteration toward more water-wetness, , electrical double layer expansion at the rock surface in contact with the aqueous phase, migration of fines, , variations in interface viscoelasticity, formation of microdispersions, , and multi-component ionic exchange. , As mentioned above, a number of studies have investigated the effects of various divalent ions on the recovery process. Findings from such studies have demonstrated that wettability alteration, ,,, IFT reduction ,,, electrical double layer expansion, , rock dissolution, ,,, and change the surface electrical charge according to zeta potential measurement ,, play a key role in oil production from carbonated rocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, among EOR methods, smart water flooding has attracted special attention because not only is it a cost-effective method, but also it has fewer environmental problems (Alipour Tabrizy et al 2011;Abubacker et al 2017;Austad 2013;Darvish Sarvestani et al 2019). Smart water flooding can be defined as a novel EOR technique in which the ionic composition of brine is changed by adding or removing ions to yield higher oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Smart water flooding can be defined as a novel EOR technique in which the ionic composition of brine is changed by adding or removing ions to yield higher oil recovery. Smart water is obtained by adjusting and optimizing the concentration of ions in the base fluid or by adding a salt containing the ions that can change the balance of the oil/brine/rock system and improve oil recovery (Austad 2013;Abubacker et al 2017; Edited by Yan-Hua Sun Darvish Sarvestani et al 2019;Manshad et al 2016). Smart water can change the wettability of the rock surface from hydrophobic to hydrophilic and reduce interfacial tension (IFT), hence allowing trapped oil to move easily (Al-sofi and Yousef 2013;Honarvar et al 2020a;Manshad et al 2017;Mohanty and Chandrasekhar 2013;Nowrouzi et al 2019;Saeedi Dehaghani and Badizad 2019;Saeedi Dehaghani et al 2020).…”
Section: Introductionmentioning
confidence: 99%